Study on cracking process of hot pressed tee based on Fick's second law. (April 2022) - Wei, Yuwei; Zhu, Xishan; Deng, Chenquan; Dai, Jinzhe; Kuang, Yunkun; Zhang, Xiaobin; Liu, Chun; Wang, Ruina; Huang, Qinghua
Highlights: Microstructure near the crack is a large amount of ferrite + a small amount of pearlite. The carbon content in the surface layer of decarburized layer is calculated by Fick's second law. The fracture surface is covered with a layer of oxide. The accident is due to the cracking in the early stage of decarburization during the pressing process. Abstract: The microstructure, composition, hardness, stress and crack morphology of cracked tee in petrochemical plant were analyzed by optical microscope, scanning electron microscope, energy spectrum analysis and finite element analysis. The carbon content of decarburized layer was calculated by Fick's second law combined with Gauss error function. The accident tee was cracked due to decarburization. The decarburization stage is determined by morphology and composition analysis. The results show that the hardness near the crack is low, only a large amount of ferrite is left in the metallographic structure, and the content of pearlite is very little, which indicates that decarburization occurs during the manufacturing of the tee. Fick's second law combined with Gauss Error Function calculation proves that the carbon content is very low, resulting in the decrease of hardness. Through the finite element calculation, the stress near the crack is the largest. In addition, the crack is covered with a layer of uniform oxide, which proves that the crack occurrs in the early stage of pressing, decarburization and oxidation in the subsequent heat treatment process. Finally, the stress concentration occurres near the open crack, resulting in liquid leakage under the action of external liquid pressure in the process of hydrostatic test. This paper provides a method for researchers to calculate the carbon content of decarburization and judge the decarburization time.